A novel method for identifying Chlamydomonas reinhardtii (Chlorophyta) and closely related species from nature. Issue 1 (21st December 2022) - Ford, Scott A.; Craig, Rory J.; Ness, Rob W.
Abstract : Here, we introduce a new method for efficiently sampling Chlamydomonas reinhardtii and closely related species using a colony PCR‐based screen with novel primer sets designed to specifically detect these important model microalgae. To demonstrate the utility of our new method, we collected 130 soil samples from a wide range of habitats in Ontario, Canada and identified 33 candidate algae, which were barcoded by sequencing a region of the rbc L plastid gene. For select isolates, 18S rRNA gene and YPT4 nuclear markers were also sequenced. Based on phylogenetic and haplotype network analyses of these three loci, seven novel isolates were identified as C. reinhardtii, and one additional isolate appeared to be more closely related to C. reinhardtii than any other known species. All seven new C. reinhardtii strains were interfertile with previously collected C. reinhardtii field isolates, validating the effectiveness of our molecular screen.